Simple Multitasking Sensors-Actuators-Transducers Based on Arduino - Nanang Suwondo, Hassan K. Juwhari, Dwi Sulisworo (International Journal of Advanced Science and Technology, 2020)
The use of a smart and simple sensor in physics education is increasing rapidly. The purpose of this paper is to describe the development of simple multitasking sensors, actuators, and transducers. Instrumentation multitasking sensors, actuators, and transducers have been developed based on Arduino mega 2560 with FreeRTOS_AVR. Commands and data are transmitted and received wireless serially by Arduino and laptop through the Bluetooth module. Then, the results are displayed in the form of graphical icons, and visual indicators made using Processing 3. It allows the environment to interact with the system. The results show that visual assessment has been confirmed with the system performing as designed to do. Besides, the developed software code is proven suitable for installation on the Arduino MEGA2560.